Cross-centre replication of suppressed burrowing behaviour as an ethologically relevant pain outcome measure in the rat: a prospective multicentre study - Wodarski, Rachel; Caspani, Ombretta; Treede, Rolf-Detlef (Pain, 2016)
Burrowing, an ethologically relevant rodent behaviour, has been proposed as a novel outcome measure to assess the global impact of pain in rats. In a prospective multicentre study using male rats (Wistar, Sprague-Dawley), replication of suppressed burrowing behaviour in the complete Freund adjuvant (CFA)-induced model of inflammatory pain (unilateral, 1 mg/mL in 100 µL) was evaluated in 11 studies across 8 centres. Following a standard protocol, data from participating centres were collected centrally and analysed with a restricted maximum likelihood-based mixed model for repeated measures. The total population (TP—all animals allocated to treatment; n = 249) and a selected population (SP—TP animals burrowing over 500 g at baseline; n = 200) were analysed separately, assessing the effect of excluding “poor” burrowers. Mean baseline burrowing across studies was 1113 g (95% confidence interval: 1041-1185 g) for TP and 1329 g (1271-1387 g) for SP. Burrowing was significantly suppressed in the majority of studies 24 hours (7 studies/population) and 48 hours (7 TP, 6 SP) after CFA injections. Across all centres, significantly suppressed burrowing peaked 24 hours after CFA injections, with a burrowing deficit of −374 g (−479 to −269 g) for TP and −498 g (−609 to −386 g) for SP. This unique multicentre approach first provided high-quality evidence evaluating suppressed burrowing as robust and reproducible, supporting its use as tool to infer the global effect of pain on rodents. Second, our approach provided important informative value for the use of multicentre studies in the future.